Designing ornament: the Plic Plac series - Crutchfield, Whitney Elizabeth-Simon, author; Lundberg, Thomas R., advisor; Coronel, Patricia, committee member; Emami, Sanam, committee member; Littrell, Mary Ann, committee member (Colorado State University. Libraries, 2010)
Ornament, "something that lends grace or beauty," and decoration, "something that adorns or enriches," are by no means new elements within the human experience. Humans have been adorning their dwellings and possessions as early as 30,000 B.C., as seen in the Grotte Chauvet in present-day France, where inhabitants decorated their caves with paintings of horses. Ornamentation has continued throughout history and within every known culture, as demonstrated by a range of objects and environments, from Paleolithic carved antlers to the interiors of the palace at Versailles. Despite this ubiquity, the terms ornament and decoration often seem unwelcome in the traditional art canon. Recent history has seen a serious attempt at the eradication of ornament, founded upon perceived associations of ornament with otherness, irrationality, weakness, and barbarism. For many practitioners of art movements during the last one hundred years, ornament and its color and complexities represented a threat to their core artistic values. Especially within the contexts of modernism and minimalism of the last century, these words appear to be reserved for those objects and ideas undeserving of the high praise given to the traditional arts, and they often provoke scoffs and disregard from art professionals and critics. This disregard comes at a cost, that being the nearly total rejection of our visual histories. While a majority of art and design movements of the last century have attempted to diminish the importance of ornament within our daily lives, it is my goal to contribute to the re-introduction of ornament that can be seen today in a number of different design and art movements focusing on the revival and celebration of ornament.
Keywords: textile; screenprint; installation; furniture; design; chair; Decoration and ornament; Chair design; Furniture design